AB111. Genetic variations rs11892031 and rs401681 are associated with bladder cancer risk in a Chinese population - Zhang, Yu (Transl Androl Urol, 2016)
OBJECTIVE: Genome-wide association studies (GWAS) have identified a number of genetic variants associated with risk of bladder cancer in populations of European descent. METHODS: we assessed association of two of these variants, rs11892031 (2q37.1 region) and rs401681 (5p15.33 region) in a Chinese case-control study, which included 367 bladder cancer cases and 420 controls. RESULTS: We found that the AC genotype of rs11892031 was associated with remarkably decreased risk of bladder cancer [adjusted odds ratio (OR), 0.27; 95% confidence interval (CI), 0.09–0.81; P=0.019), compared with the AA genotype of rs11892031; and that CT/CC genotypes of rs401681 were associated with significantly increased risk of bladder cancer (adjusted OR, 1.79; 95% CI, 1.10–2.91; P=0.02), compared with the TT genotype of rs401681. We further conducted stratification analysis to examine the correlation between single nucleotide polymorphism (SNP) rs11892031/rs401681 and tumor grade/stage. Results showed that heterogeneity in ORs of tumor categories was not significant for either rs11892031 or rs401681 (P>0.05), indicating that the two SNPs seemingly do not associate with tumor grade and stage of bladder cancer in our study population. CONCLUSIONS: The present study suggests that the SNPs rs11892031 and rs401681 are associated with bladder cancer risk in a Chinese population.